Surgery-First Accelerated Orthognathic Surgery: Postoperative Rapid Orthodontic Tooth Movement - Liou, Eric J.W.; Chen, Po-Hsung; Wang, Yu-Chih; Yu, Chung-Chih; Huang, C.S.; Chen, Yu-Ray (Journal of oral and maxillofacial surgery, 2011)
Clinically, we have observed the phenomenon of postoperatively accelerated orthodontic tooth movement in patients who had orthognathic surgery. This phenomenon lasts for a period of 3 to 4 months. However, the underlying mechanisms of this phenomenon have not been well studied yet. The purpose of this prospective clinical pilot study was to study the postoperative changes in bone physiology and metabolism and the corresponding responses in the dentoalveolus, such as the changes in tooth mobility. Twenty-two consecutive adult patients who had 2-jaw orthognathic surgery were included in this study. The levels of serum alkaline phosphatase and C-terminal telopeptide of type I collagen (ICTP), as well as the tooth mobility of the maxillary and mandibular incisors based on the Periotest method (Siemens AG, Bensheim, Germany), were examined preoperatively and 1 week, 1 month, 2 months, 3 months, and 4 months postoperatively. The data were analyzed statistically. Both tooth mobility of the maxillary and mandibular incisors and ICTP significantly increased from 1 week to 3 months postoperatively and then decreased to their preoperative levels in the fourth month postoperatively. The changes in tooth mobility were significantly in correspondence with the changes in ICTP. The alkaline phosphatase level significantly increased from the first to fourth month postoperatively, but it was not significantly correlated to the changes in tooth mobility. The orthognathic surgery triggers a 3- to 4-month period of higher osteoclastic activities and metabolic changes in the dentoalveolus postoperatively, which possibly accelerates postoperative orthodontic tooth movement.